Design and Fabrication of a Pedal-Powered Clay Milling Machine. - Ijuka, Catherine (Kabale University, 2024)
Clay powder is a raw material mixed with sand and water as a binder during the making of molds for sand casting in the foundry workshops. Clay powder is produced through milling of the dry solid clay particles of 5mm diameter to produce 0.002mm diameter clay particles as the final clay powder. On the market, several milling machines have been introduced for milling clay, but most small-scale particles still use traditional means due to the high costs associated with these machines. This design is aimed at providing a less costly machine to small-scall foundry workshops. This project focuses on the design and development of a pedal-powered clay milling machine intended for foundry workshops that utilize clay as a binder in sand casting. The machine employs the grooved disc mills to crush clay into fine particles, ensuring consistent material quality for foundry applications. Powered by human pedaling, the system generates 100 watts of input power, efficiently transferred through a chain drive to the milling mechanism. The design prioritizes simplicity, cost-effectiveness, and sustainability, making it accessible for small-scale foundry workshops. By integrating ergonomic considerations, the pedal-powered clay milling machine offers a reliable and eco-friendly solution for producing clay powder.